PELAKSANAAN PENGAWASAN DAN PENGAMATAN TERHADAP POLA PEMBINAAN ANAK OLEH HAKIM PENGAWAS DAN PENGAMAT PENGADILAN NEGERI MEDAN - Kurniati Siregar (jurnal.unprimdn.ac.id, 2021)
According to Article 277 of KUHAP, Supervisory Judge and Observer are assigned to help the Head of Court do supervision and observation on court’s verdicts on imprisonment. According to SEMA No. 7/1985 on Operational Manual of the Tasks of Supervisory Judge and Observer, the visit of a Judge to Penitentiary should be once in three months to examine the truth of the Minute of the Implementation of court’s verdict, to gather the prisoners’ data, to interview wardens and prisoners concerning treatment of prisoners. The result of the research in the Medan District Court and LPKA Medan showed that the implementation of supervision and observation done by supervisory judges and observers of the Medan District Court on prisoners in LPKA was not optimal. The judges only visited LPKA once in six months, the child prisoners who wanted to be interviews had already been prepared by LPKA management. Some obstacles were as follows: law does not regulate the tasks of judges, there was lack of supervisory judges and observers, judges were burdened by limited time and work load, there was double standard (dualism) in the institutional system in implementing supervision and observation, and there was lack of facility and infrastructure.